The Influence Of Organisational Culture On Organisational Commitment, Transformational Leadership, And Competitive Advantage After Business Consolidation - Fery Permana; Gatot Kustyadji (Journal of Managerial Sciences and Studies, 2024)
The purpose of this study is to analyze the relationship pattern between organizational culture, organizational commitment, transformational leadership, and competitive advantage. The study was conducted on consolidated State Owned Enterprises manufacturing companies in Indonesia, namely PT. X (Persero) Tbk, which includes PT. A, PT. B, and PT. C. Consolidation was done in achieving the vision and mission of the company as a leading cement company in Indonesia and Southeast Asia. This study used respondents of 121 managers with a stratified random sampling technique. Partial Least Square was used for data analysis. The results suggested that there is a significant positive effect between; (a) organizational culture on organizational commitment, (b) organizational culture towards transformational leadership, (c) organizational culture competitive advantage, (d) organizational commitment towards competitive advantage, and (e) transformational leadership towards competitive advantage